Proteomic approximation of differential expression in pleurotus ostreatus (oyster fungus) as a response to bioaccumulation of lead (Pb) - Huaraya-Chambi, Froilan Rodolfo (2024)
In recent years there has been considerable progress in environmental biotechnology, in the use and application of different living organisms for the bioremediation of different compounds, on many occasions it’s of toxic nature in contaminated sites or media, these bioremediation processes offer high specificity in the removal in both in situ and ex-situ systems. The use of white rot fungi in heavy metal bioremediation processes is a very promising environmental technology, the studies of it focus on the ability to degrade ubiquous compounds. The purpose of this research is to try to decipher which are the key elements of the molecular genetics of Pleorotus ostreatus that make it tolerant and allow its accumulation of heavy metals such as lead (Pb), from a differential proteomic approach perspective. The methodology is divided into three stages: 1.- purification; obtaining the crude extract: precipitation with 90% ammonium sulfate, and hydrophobic interaction chromatography. Tandem mass spectrometry ESI-CID-MS/MS 3.- Bioinformatic analysis using DNA Star software, in which sequential homology studies were performed to know the structural character of the proteins. Through the results of differential proteomic approach (protein molecular mass of ~34 kDa), we have been able to establish that manganese peroxidase oxidative enzymes are found in their expression levels, showing a high degree of homology and identity of conserved regions in the alignments of the sequenced peptides, so we can suggest that these enzymes are extremely important for the processes of bioaccumulation of heavy metals (Pb). Furthermore, the geographical distribution could probably reveal some mutations in this family of proteins, trying to infer the participation of each amino acid along the polypeptide chain, which couldn’t be found in the consensus region of the sequence but in the variable regions. Further studies of site-directed mutagenesis could reveal valuable information about this family, which is crucial in bioremediation processes from a biotechnological perspective.